The epidemiology of hookworm infection and its contribution to anaemia among pre-school children on the Kenyan coast. - Brooker, S; Peshu, N; Warn, P; Mosobo, M; Guyatt, H; Marsh, K; Snow, R (1999)
Intestinal nematode infections are recognized as a major public health problem, and helminth control is currently being directed towards school-aged children who are known to harbour the heaviest infections and are most likely to suffer from associated morbidity. However, few data are available for the epidemiology of intestinal nematodes in pre-school children in Africa, and the contribution of hookworm infection to the aetiology and severity of anaemia among pre-school children remains poorly understood. This paper investigates the epidemiology of parasitic infections in 460 pre-school children who were part of a larger case-control study of severe malaria in Kilifi on the Kenyan coast. Almost one-third (28.7%) were infected with hookworm, 20.2% with Ascaris lumbricoides and 15.0% with Trichuris trichiura. Infection prevalence of each species rose with age, and the prevalence of heavy infection with hookworm and mean intensity of hookworm were markedly age-dependent. One-third (34.3%) of children had malaria. Overall, 76.3% of children were anaemic (haemoglobin < 110 g/L), with the prevalence decreasing with age. Anaemia was significantly worst in children with heavy hookworm infection (> 200 eggs per gram). This relationship held for all ages, both sexes, and was independent of socioeconomic factors. The application of attributable morbidity methods confirmed the contribution of hookworm infection to anaemia.